The dead yard : tales of modern Jamaica - Thomson, Ian, 1961- (London : Faber and Faber, 2009)
"Jamaica used to the source of much of Britain's wealth, an island where slaves grew sugar and the money flowed out in vast quantities. It was a tropical paradise for the planters, a Babylonian exile for the Africans shipped to the Caribbean. Since independence in 1962, it has gradually become associated with a new kind of hell, a society where extreme violence has become ordinary and gangs control the areas where most Jamaicans live. Ian Thomson's brave new book explores a country of lost promise, a country that most older Jamaicans in Britain cannot recognise as their own. Once a beacon of optimistic third world politics, the island is now sunk in corruption, hopelessness and drug wars. Jamaica's music was once the lilting anthem of idealists everywhere; now it is a repetitive glorification of homophobia and violence"--Global Books in Print.
(Black man) in Hammersmith Palais -- Trench town mix up -- Strictly come dancehall -- Slaving -- Massa day done? -- I've got to go back home -- Forward unto Zion -- Maximum black -- Stranded on death row -- The Negotiator -- Blood and fire -- Revival time -- Don't call us immigrants -- English upbringing, background Caribbean -- Everything crash -- Nanny knew best -- The Killing of a Chinese shopkeeper -- 007 (Shanty Town) -- Sitting in limbo -- Police and thieves -- Night nurse -- Scotland Yard -- Herbsman hustle -- Investors in people ('Cargo') -- Lord creator -- Life of contradiction.
Includes bibliographical references (pages 350-356) and index.
NLJCols20082021
Keywords: Jamaica -- Description and travel; Jamaica -- Social conditions -- 21st century; Jamaica -- Moral conditions; Jamaica -- History -- 1962-; Jamaica -- Politics and government -- 1962-; Moral conditions; Politics and government; Social conditions; Travel; Jamaica; Since 1962; Jamaica -- Description and travel; History